PENGARUH SUKU BUNGA, PENDAPATAN DAN ARUS KAS TERHADAP STRUKTUR MODAL PADA PT. NILAM WANGI MEDAN PERIODE 2013-2017 - Dina Rosmaneliana (JURNAL ILMIAH MAKSITEK, 2018)
Company must have purposes to gain profit in order to survive continuity of company for long term and company is to maximized profits to increase growth of company. On the other side, need a correction to know company’s achievements during a certain period, this is useful to take action that will be company do in the future that still in line with the purpose of company. The purpose of this study was to determine and analyze the effect of interest rate, revenue and cash flow towards capital structure at PT. Nilam Wangi Medan period 2013-2017. This method of research is using multiple linear regression analysis with SPSS software. The result showed that interest rate, revenue and cash flow simultaneously and significantly positive effect towards capital structure at PT. Nilam Wangi Medan period 2013-2017. In determination coefficient (Adjusted R2) variations in variable interest rate, revenue, cashflow is 14,5% towards capital structure at PT. Nilam Wangi Medan period 2013-2017 and the rest are influenced by other variables that is not explained in this study such as liability,etc. Interest rate partially negative effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017. revenue partially positive effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017. Cash flow partially positive effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017.